Pembentukan Gaya Hidup Pada Penderita Hipertensi ( Self Care Management ) Sesuai Dengan Penerapan Teori Dorothea E. Orem - Rukmana, Melinda Siti; Ummi Malikal Balqis , Ummi (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2022)
Hypertension is the condition when the blood pressure against the artery wall is too high. Hypertensive disease usually requires self-care management to form independence toward lifestyle changes for sufferers. Self-care management is an optimal action to maintain health that is carried out independently by a person to meet the needs of life to improve and regulate the function of the individual. In the application of self-care management Dorothea E. Orem has a significant effect in controlling blood pressure. The establishment of nursing care within a certain terrorist framework is important in terms of contributing to improving the quality of service. The purpose of this case study is to build the independence of hypertensive patients by applying Orem's self-care management theory, the case involves a 44-year-old adult woman who suffers from hypertension due to an unhealthy lifestyle. Dorothea E. Orem's theory is important in improving the quality of health in hypertension cases.